2020
DOI: 10.1016/j.ijantimicag.2020.105947
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: fear versus data

Abstract: Highlights Comparison of incidence and mortality rates of four common coronaviruses circulating in France with those of SARS-COV-2 in OECD countries. As of 2 March 2020, 90 307 patients had tested positive for SARS-CoV-2 worldwide, with 3086 deaths (mortality rate 3.4%). As of 2 March 2020, among OECD countries, 7476 patients had tested positive for SARS-CoV-2, with 96 deaths (mortality rate 1.3%)  As of 2 March 2020, in France, 191 people had tested positive for SARS-CoV-2, with three deaths (mortality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 26 publications
0
63
1
5
Order By: Relevance
“…Vaccination past the peak of infections and long-term school closures late in the outbreak appear less cost-effective, underscoring the importance of timing. Roussel et al (2020) reported a mortality rate of 1.3% in OECD countries as of March 2, 2020. Onder al.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination past the peak of infections and long-term school closures late in the outbreak appear less cost-effective, underscoring the importance of timing. Roussel et al (2020) reported a mortality rate of 1.3% in OECD countries as of March 2, 2020. Onder al.…”
Section: Discussionmentioning
confidence: 99%
“…However, since asymptomatic carriers of SARS CoV-2 are highly infectious, the societal consequences of achieving herd immunity may be devastating [34]. Moreover, other coronaviruses may also stimulate population immunity in the pharynx of asymptomatic individuals that are not regularly systematically tested around the world [5].…”
Section: Surveillance Diagnosis and Treatment Of Covid-19 In Nigeriamentioning
confidence: 99%
“…The basis of managing COVID-19 with cocktails of drugs is because viral infections are ecosystem infections, where the outcomes depend on inoculums and surrounding microbiota, which is often bacterial [5]. This highlights why there is a need for antibiotic stewardship programs in Nigeria to help preserve the efficacy of commonly used antibiotics.…”
Section: Surveillance Diagnosis and Treatment Of Covid-19 In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Limited understanding of the diverse range of tissues targeted by the virus and its potential receptors, there is an immediate need to understand SARS-CoV-2 entry mechanism and pathogenesis to develop effective therapeutics. It is recently identi ed that trimeric transmembrane spike glycoprotein of SARS-CoV-2 and SARS-CoV that share a high degree of similarity within the RBD, binds to the common human ACE-2 receptor, yet SARS-CoV-2 is highly infectious than SARS-CoV [22]. To investigate the difference in these highly similar spike proteins, we analyzed the phyletic relatedness of the spike proteins from coronaviruses that are known to infect humans.…”
Section: Molecular Docking and Simulationsmentioning
confidence: 99%